2022
DOI: 10.1002/pul2.12128
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between thermodilution and Fick methods for resting and exercise‐induced cardiac output measurement in patients with chronic dyspnea

Abstract: Studies comparing thermodilution (TD) and the direct Fick method (dFM) for cardiac output (CO) measurement are rare. We compared CO measurements between TD (2-5 cold water injections), the dFM, and indirect Fick method (iFM) at rest and during exercise, and assessed the effect of averaging different numbers of TD measurements during exercise. This retrospective study included 300 patients (52.3% women, mean age 66 ± 11 years) having pulmonary hypertension (76.0%) or unexplained dyspnea. Invasive hemodynamic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Cardiac output measurement using indirect Fick is frequently used in clinic. However, the agreement between IF and TD for patients with PH or suspicion of PH is poor with LoA ranging between 1.8 L/min to 4.1 L/min and bias ranging between 0.4 L/min and −0.8 L/min [ 5 , 12 , 13 , 14 ]. Comparisons of indirect Fick with DF in PcPH are lacking [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac output measurement using indirect Fick is frequently used in clinic. However, the agreement between IF and TD for patients with PH or suspicion of PH is poor with LoA ranging between 1.8 L/min to 4.1 L/min and bias ranging between 0.4 L/min and −0.8 L/min [ 5 , 12 , 13 , 14 ]. Comparisons of indirect Fick with DF in PcPH are lacking [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…CO measurement using thermodilution (TD, CO TD ) widely replaced CO DF in the field of PH based on the results of one study comparing CO TD against CO DF and demonstrating acceptable agreement between the two methods in 35 PcPH patients [2]. Recent studies, however, did not confirm the previous results and demonstrated a poorer agreement between CO TD and CO DF using Bland and Altman (BA) analysis for patients with PcPH [3,4], or with a suspicion of PH [5].…”
Section: Introductionmentioning
confidence: 99%